Is Serum VEGF-A Level an Indicator of Early-Onset Poststroke Depression? - Uslu, Emine Yildirim; Yildiz, Sevler (Mdpi, 2024)
Background and Objectives: Poststroke depression (PSD) is a psychiatric complication occurring after a stroke, and is known to negatively impact quality of life. In the present study, the possible relationship between serum vascular endothelial growth factor (VEGF-A) levels and early-onset PSD, as well as the predictive value of serum VEGF-A levels for early-onset PSD, were investigated. Materials and Methods: The study included 88 individuals diagnosed with acute ischemic stroke (AIS). Demographic data, clinical characteristics, and serum VEGF-A levels were recorded, and radiological images were examined to determine the lesion locations. The National Institutes of Health Stroke Scale (NIHSS), Montreal Cognitive Assessment (MoCA), and Hamilton depression scale (HAMD-17) were administered to the patients. Furthermore, serum VEGF-A levels were measured in all participants. Results: Although the body mass index (BMI) and VEGF-A levels were similar between the groups, MoCA scores were lower [(19.2 +/- 4.4) vs. (22.3 +/- 3), p = 0.001] and NIHSS scores were higher [18 (8-28) vs. 14 (3-24), p = 0.006] in individuals with PSD than in those without it. When the patients with PSD were categorized into three groups, patients with severe PSD had higher NIHSS scores [26 (23-27) vs. 15 (8-23), p = 0.006] and lower MoCA scores [(14.3 +/- 1) vs. (20.9 +/- 3.8), p = 0.005] than those with mild PSD. Moreover, VEGF-A levels and lesion localization were similar between mild, moderate, and severe PSD groups (p = 0.130). The MoCA score was negatively (r = -0.498, p < 0.001) correlated and the NIHSS score was positively correlated (r = 0.497, p < 0.001) with the HAMD-17 score. Conclusions: Our findings suggest that longitudinal studies in large cohorts including healthy control groups are needed to examine the possibility of using serum VEGF-A level as a marker for predicting early-onset PSD.
Keywords: poststroke depression; vascular endothelial growth factor; early-onset poststroke depression; lesion location